2021
DOI: 10.1021/acs.jafc.0c06058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-Tobacco Mosaic Virus/Fungicidal/Insecticidal/Antitumor Bioactivities of Natural Product Hemigossypol and Its Derivatives

Abstract: To further study the structure−activity relationship of gossypol, hemigossypol (1) and its derivatives (2−23) were successfully designed via structure simplification and chemically synthesized. The anti-tobacco mosaic virus (TMV), fungicidal, and insecticidal activities of them were tested systematically. Most of these derivatives exhibited excellent anti-TMV activity. Furthermore, these compounds also exhibited broad-spectrum fungicidal activities against 14 kinds of phytopathogenic fungi. In particular, hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…TMV was According to Gooding’s method[23], TMV virions maintained in N. tabacum cv. K326 were extracted and purified from the harvested leaves of systemically inoculated seedlings by homogenization in 0.01 M PBS (phosphate-buffered saline) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…TMV was According to Gooding’s method[23], TMV virions maintained in N. tabacum cv. K326 were extracted and purified from the harvested leaves of systemically inoculated seedlings by homogenization in 0.01 M PBS (phosphate-buffered saline) buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al . found some β-carboline analogues 7 , hemigossypol 13 , dehydrobufotenine derivatives 14 , pityriacitrin marine alkaloids 15 , pulmonarin alkaloids 16 and hamacanthin derivatives 17 exhibited higher anti-TMV activities than ningnanmycin. Many other natural alkaloids derivatives were also developed as potential TMV inhibitors 18 27 .…”
Section: Introductionmentioning
confidence: 98%
“…8,9 Meanwhile, an increasing number of antiplant virus agents are being discovered and developed from natural products. [10][11][12] Ferulic acid, a kind of natural phenolic acid, was isolated from fruits and vegetables. 13 It has been reported that ferulic acid and its derivatives have various biological activities, including antiviral, 14 antibacterial 15 and herbicidal activities.…”
Section: Introductionmentioning
confidence: 99%